Gender Relation in Willow Trees Don’t Weep Novel (2014) by Fadia Faqir: A Feminist Literary Criticism - Ida Rosida; Aini Soraya (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2017)
This study is aimed at finding gender relations between male and female character as they are depicted in Willow Trees Don’t ’Weep (2014) novel written by Fadia Faqir. This study employs descriptive qualitative method on feminist literary criticism as a theory to find and reveal gender issues. The text is analyzed by using feminist criticism “woman as reader” to give the evaluation and interpretation on how woman writes about woman. The result shows that there are three significant points in which gender relation in patriarchal culture is portrayed in the novel. They are male domination, discrimination towards women, and violence against women. The results were evaluated by examining female character’s condition in a patriarchal society through woman’s point of view based on her social life and experiences. Moreover, the country where women live is influenced the gender relation. Jordan in this case, has the strongest patriarchal system compared to Pakistan, Afghanistan, and London (the countries where Najwa lived while searching for her father).DOI: 10.15408/insaniyat.v2i1.6586